The Influence of Social Support for Online Learning Motivation - Azrin Raimi, Ahmad; Nur Adibah, Zamri; Muhammad Harriz, Zaini; Eliyas, Sulaiman Mohandas; Dean Yeo, Kai Liang; Noor Hanim, Rahmat (RSIS International, 2026)
Online learning continues to expand due to its accessibility and flexibility; however, sustaining learners’ motivation in digital environments remains a challenge. This study aims to investigate the influence of social support on learners’ motivation to learn online, alongside the roles of expectancy and value. A quantitative survey design was employed, involving 255 respondents from two Malaysian public universities representing the Science & Technology and Social Sciences & Humanities clusters. The instrument consisted of 37 items adapted from Vroom’s Expectancy Theory (1964) and Fowler’s Motivation to Learn Online Questionnaire (2018), and demonstrated strong reliability (overall Cronbach’s α = .937). Findings show that learners perceived high levels of instructor support, strong task value, and strong control of learning beliefs, although their self‑efficacy and social engagement varied depending on task complexity and online interaction. Correlation analyses revealed strong positive relationships among expectancy, value, and social support, indicating that online learning motivation is shaped collectively by cognitive beliefs and interpersonal support. No significant differences were found across universities or clusters. The study highlights the importance of emotional, instructional, and peer‑based support in fostering a more engaging and motivating online learning experience.